Compound Words Found in Seventy-Seven Thousand Service-Trees (Sri Chinmoy) (e-Journal of Linguistics, 2020)
This research deals with compound words usedin Seventy-Seven Thousand Service-Trees by SriChinmoy. The case is many people did not recognizeand aware of using it. This research is trying todescribe the types and the structure of compoundwords and supported by two theories, those are Booij(2007) and McCarthy (2002). In achieving theobjectives, the researcher uses descriptive qualitativeas the type of the research. The data are in the form ofcompound words. In collecting the data the writerapplies documentation technique and the steps arereading attentively, selecting, collecting, andclassifying the data systematically by following thetypes and the structure of compound words. The resultsof this research show that there are three kinds ofcompound words. From 390 the data of compoundwords, there are 348 data are classified as a compoundnoun, 20 data are classified as a compound adjective,and 22 data are classified as a compound verb. In thisresearch, it is found that only two ways in the spellingof compound words are solid and hyphenated. Thereare three sub-classes of compound words found in thisstudy those are endocentric compound, exocentriccompound, and copulative compound.